Media Pembelajaran Berbasis Mobile Tajwid Pada Lembaga Bimbingan Masuk Gontor dengan Metode Demonstrasi - Hisnu Al Mujahidin; Dihin Muriyatmoko; Jumhurul Umami (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2020)
The Darussalam Gontor Islamic Boarding School graduates established a tutoring institution for prospective students who wish to enter Gontor in their respective regions. The institution is called the Gontor Entrance Guidance Institute. Prospective students who want to enter Gontor do not all pass the oral exam, one of the factors is the difficulty in tajwid lessons. At the Gontor entrance guidance institution, tajwid learning currently uses a limited number of printed books, making it difficult for those who want to learn it. Among them are Gontor entrance guidance agencies, branch cottages and alumni lodges. For that we need other learning media that can solve these problems, one of which is the mobile smartphone media. The purpose of this research is to make it easier for prospective students who want to learn the Gontor version of Tajwid. The implementation of this application uses a waterfall approach and applies a demonstration method. Testing the Tajwid 2 application is done in 6 ways. With the blackbox method, it shows the application is running smoothly. The use of hardware with six smartphones of various brands and screen sizes indicates the application is running well. A learning media expert gave an average rating of 94%. Tajwid teachers about learning materials by distributing questionnaires to 6 respondents who gave good feedback with a value of 87%. Prospective students about learning materials by distributing questionnaires to 15 respondents who gave good feedback with a value of 88.5%. General Google Playstore users scored 4.9 out of 5 (highest total rating) totaling 112 reviews (https://play.google.com/store/apps/details?id=com.konu.tajwid). The results of the questionnaire show that this application is very helpful, it can be an effective learning tool, but the application is only helpful, it cannot replace the role of the teacher and the interaction between teachers and real students.